Nurturing Higher Order Thinking Skills Among Malay Language Teachers Through Lesson Study - Noel Jimbai Balang; Zamri Mahamod; Nor Aishah Buang (Journal of Learning Improvement and Lesson Study, 2021)
The aim of this study is to identify higher order thinking skills (HOTS) among Malay language (ML) teachers through a lesson study. Two aspects were explored in order to answer the research questions, namely the nurturing of HOTS and the teaching attitude towards the implementation of the lesson study at school. Qualitative research is the research design used by the researchers. A total of seven ML teachers acting as participants in the research. Information is obtained through triangulation methods which cover interviews, observations and analysis of documents. The data interviews were analysed and transcribed verbatimally with study participants. The findings showed that there is a deepening of teacher’s HOTS through a variety of student learning activities during teaching. The participants in the study were positive and prepared for study of the lesson. Study lessons would be more effective if the workload of the teacher is decreased. Meeting time between teaching staff involved in the study of lessons should be included in the teaching schedule. The findings of this study are therefore important to consider the development of HOTS, which can be used by all teachers in teaching to make learning more relevant to 21st century learning.